2014
DOI: 10.1002/nvsm.1499
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical framing: examining the message structure of nonprofit organizations on Twitter

Abstract: • All organizations must persuade stakeholders that they are worth supporting. Organizations need donors to give, volunteers to volunteer, consumers to purchase, and general support for public funding. Because Twitter messages are restricted to 140 characters or less, organizations' message structures must be clearer and may employ traditional rhetorical techniques such as ethos, pathos, and logos, to garner support and promote action. By using content analysis, the tweets of eight charitable organizations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
4
31
1
Order By: Relevance
“…Previous research has identified characteristics of tweets that are associated with higher levels of retweeting: for example, textual content (e.g., Araujo et al, 2015;Auger, 2014);hashtags (e.g., boyd et al, 2010;Suh et al, 2010), and interactivity (e.g., Burton and Soboleva, 2011;Li and Li, 2014). There have been mixed results on the effect of mentions on retweeting: Yang and Counts (2010) found that tweets containing mentions were more likely to be retweeted, but other authors have found that mentions decreased the number of retweets (Soboleva et al, 2015;Suh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified characteristics of tweets that are associated with higher levels of retweeting: for example, textual content (e.g., Araujo et al, 2015;Auger, 2014);hashtags (e.g., boyd et al, 2010;Suh et al, 2010), and interactivity (e.g., Burton and Soboleva, 2011;Li and Li, 2014). There have been mixed results on the effect of mentions on retweeting: Yang and Counts (2010) found that tweets containing mentions were more likely to be retweeted, but other authors have found that mentions decreased the number of retweets (Soboleva et al, 2015;Suh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advanced communication technology helps an NGO to distinguish itself from its peers by building its public image through its websites and social media presence. This in turn may make the organization more attractive as a potential partner (Auger ; Corder ; Maxwell and Carboni ).…”
Section: Discussionmentioning
confidence: 99%
“…In a competitive arena, social media has become a way for nonprofits to set themselves apart from other organizations in the same sector (Corder ). Using emergent forms of communication can help NGOs get a leg up on their competition and to persuade potential partners and stakeholders in supporting or preferring to partner with one NGO over another (Auger ; Maxwell and Carboni ). The use of technology may help in achieving clarity of expectations.…”
Section: Collaboration: Forms and Essential Elementsmentioning
confidence: 99%
“…Communicating effectively requires organisations to understand the complexity of the social media landscape, the capabilities of different platforms, their use by audiences and their suitability for communicating different types of information (Saxton and Guo 2014, Saxton and Waters 2014, Sisco and McCorkindale 2013. Content must be engaging and offer something audiences can relate to (Auger 2014). In other words, organisations must engage in ongoing connective labour, the 'largely invisible digital, immaterial, and affective labor' (Megan Boler et al 2014: 3) that characterises the strategic use of digital media to generate 'affective glue' that can hold a movement together.…”
Section: Media Coverage Of Vawg and The Promise Of Social Mediamentioning
confidence: 99%